Quantum Computing - Lala, Parag k., 1948- (McGraw-Hill Education, 2019)
A self-contained, reader-friendly introduction to the principles and applications of quantum computing. Especially valuable to those without a prior knowledge of quantum mechanics, this electrical engineering text presents the concepts and workings of quantum information processing systems in a clear, straightforward, and practical manner. The book is written in a style that helps readers who are not familiar with non-classical information processing more easily grasp the essential concepts; only prior exposure to classical physics, basic digital design, and introductory linear algebra is assumed. Quantum Computing: A Beginner?s Introduction presents each topic in a tutorial style with examples, illustrations, and diagrams to clarify the material. Written by an experienced electrical engineering educator and author, this is a self-contained resource, with all the necessary pre-requisite material included within the text. Coverage includes: Complex Numbers, Vector Space, and Dirac Notation, Basics of Quantum Mechanics, Matrices and Operators, Boolean Algebra, Logic Gates and Quantum Information Processing, Quantum Gates and Circuit, Tensor Products, Superposition and Quantum Entanglement, Teleportation and Superdense Coding, Quantum Error Correction, Quantum Algorithms, Quantum Cryptography.